Expression of Genes for a Flavin Adenine Dinucleotide-Binding Oxidoreductase and a Methyltransferase from Mycobacterium chlorophenolicum Is Necessary for Biosynthesis of 10-Methyl Stearic Acid from Oleic Acid in Escherichia coli - Machida, Shuntaro; Bakku, Ranjith K.; Suzuki, Iwane (Frontiers in Microbiology, 2017)
In living organisms, modified fatty acids are crucial for the functions of the cellular membranes and storage lipids where the fatty acids are esterified. Some bacteria produce a typical methyl-branched fatty acid, i.e., 10-methyl stearic acid (19:0Me10). The biosynthetic pathway of 19:0Me10 in vivo has not been demonstrated clearly yet. It had been speculated that 19:0Me10 is synthesized from oleic acid (18:1∆9) by S-adenosyl-ʟ-methionine-dependent methyltransfer and NADPH-dependent reduction via a methylenated intermediate, 10-methyelene octadecanoic acid. Although the recombinant methyltransferases UmaA and UfaA1 from Mycobacterium tuberculosis H37Rv synthesize 19:0Me10 from 18:1∆9 and NADPH in vitro, these methyltransferases do not possess any domains functioning in the redox reaction. These findings may contradict the two-step biosynthetic pathway. We focused on novel S-adenosyl-ʟ-methionine-dependent methyltransferases from Mycobacterium chlorophenolicum that are involved in 19:0Me10 synthesis and selected two candidate proteins, WP_048471942 and WP_048472121, by a comparative genomic analysis. However, the heterologous expression of these candidate genes in Escherichia coli cells did not produce 19:0Me10. We found that one of the candidate genes, WP_048472121, was collocated with another gene, WP_048472120, that encodes a protein containing a domain associated with flavin adenine dinucleotide-binding oxidoreductase activity. The co-expression of these proteins (hereafter called BfaA and BfaB, respectively) led to the biosynthesis of 19:0Me10 in E. coli cells via the methylenated intermediate.